RECIPROCAL DETERMINISM "DAKOCAN" CHALLENGE EFFORTS TO REDUCE HIV AND AIDS CASES IN JEMBER DISTRICT - Mury Ririanty; Thohirun Thohirun; Iken Nafikadini (UNEJ e-Proceeding)
Data from Jember District Health Office of 2004 untilDecember 2015 retrospective case series of HIV andAIDS reach 2309. The risk factors of HIV and AIDS arehighest, heterosexual (2007 people), Gay (155),injecting drug users (57 people), perinatal (66).Blood transfusion (4) and bisexual (2 people). Whilethe group of age with HIV and AIDS is highestproductive age is the age of 25-49 years, 20-24years, 15-19 years. Looking at the data above can beseen that the greatest number of cases that are inthe productive age and heterosexual. Heterosexualactivity can occur through sexual behavior. Whileheterosexual actors not only in pair remains couldalso be on the couple did not stay so can be called asa free sex. The perpetrators are non-sexual is notonly found in locations diinikasikan as a place ofprostitution although the county Jember. Certainjobs in the informal sector can not be deniedcontributor numbers of cases of HIV and AIDS. Likeas Female Sex Workers either directly or indirectly.Heterosexual activity can occur through sexualbehavior. While heterosexual actors not only in pairremains could also be on the couple did not stay socan be called as free sex. The perpetrators are nonsexualis not only found in locations like aprostitution. And Dakocan one of informal sector.This is because the work activities that are in acoffee stall selling coffee and peddle an informalsectorThe phenomenon of "Ngobar" or drinking coffeetogether that appears to be a new history that hasbeen reconstructed, not just the level of socialorientation, aesthetic pattern and a distinctive style,but now more and more functions get their ownspace in the hearts of people of various ages fromteenagers to the elderly. In addition to affordable,aesthetic value "coffee together" is also a form ofentertainment that is irreplaceable from public life.Coffee culture, especially drinking together is notonly in Indonesia whose territory coffeemanufacturers such as Tulung, Aceh, Jogjakarta,Ponorogo, Bali and various other areas but haspenetrated almost all areas especially crowdedbecause of his public activity included in Jember.Coffee is not just a hobby or pleasure alone, insidefrequent exchange of information and discourse,even common knowledge development cooperationagreements ranging from advanced appointmentuntil contract signature that produce economicvalue. [Thohirun et all, Proceedings Symposium ofNational A Health Communication]. There are manycontributing factors causing this culture grown toinclude activities other than just drinking coffeeespecially sex activities. These factors can also beformed reciprocally.According to psychologist Albert Bandura, reciprocaldeterminism is a model composed of three factorsthat influence behavior: the environment, theindividual, and the behavior itself. Essentially,Bandura believes that an individual's behaviorinfluences and is influenced by both the social worldand personal characteristics [Bandura, Sociallearning theory]. The environmental component ismade up of the physical surroundings around theindividual that contain potentially reinforcing stimuli,including people who are present (or absent). Theenvironment influences the intensity and frequencyof the behavior, just as the behavior it self can havean impact on the environment. The individualcomponent includes all the characteristics that havebeen rewarded in the past. Personality and cognitivefactors play an important part in how a personbehaves, including all of the individual'sexpectations, beliefs, and unique personalitycharacteristics. And finally, the behavior itself issomething that may or may not be reinforced at anygiven time or situation. So, Based on the preliminarystudy, the researchers have wanted to analyze howdeterminant reciprocal of dakocan. And this reasonas well as the aim of this study.